Non-integrin laminin receptor (LamR) plays a role in axonal outgrowth from chicken DRG via modulating the Akt and Erk signaling - Mrówczyńska, Ewa; Machalica, Karolina; Mazur, Antonina Joanna (Frontiers in Cell and Developmental Biology, 2024)
37/67 kDa laminin receptor (LamR)/ribosomal protein SA exhibits dual function as both a ribosomal protein and cell surface receptor for laminin. LamR influences critical cellular processes such as invasion, adhesion, and migration when acting as a receptor. Despite the acknowledged importance of LamR/67LR in various cellular processes, its contribution to the peripheral nervous system (PNS) development is obscure. Thus, this study investigated the biological activity of LamR in peripheral axonal outgrowth in the presence of laminin-1 or Ile-Lys-Val-Ala-Val (IKVAV) peptide, whose important role in dorsal root ganglia (DRG) axonal outgrowth, as we recently showed. Unexpectedly, we did not observe LamR on the surface of DRG cells or in a conditioned medium, suggesting its intracellular action in the negative regulation of DRG axonal outgrowth. Using C-terminus LamR-targeting IgG, we demonstrated the role of LamR in that process, which is independent of the presence of Schwann cell precursors (SCPs) and is mediated by extracellular signal-regulated kinase (Erk) and Protein kinase B (Akt1/2/3) signaling pathways. Additionally, we show that the action of LamR towards laminin-1-dependent axonal outgrowth is unmasked only when the activity of integrin β1 is perturbed. We believe that modulation of LamR activity provides the basis for its use for inhibiting axon growth as a potential therapeutic agent for regulating abnormal or excessive neurite growth during neurodevelopmental diseases or pathological nerve regeneration.